Late-onset enteric fistula following radical cystectomy for bladder cancer: A case report - Arthur Baudewyns; Teddy Jabbour; Henri-Alexandre Bourgeno; Alexandre Peltier; Romain Diamand (Urology Case Reports, 2023)
Enteric fistula is a rare early onset complication following radical cystectomy with urinary diversion for bladder cancer. We present the case of a 55-year-old woman presenting with an insidious fistula between the ileum and the ileal conduit, diagnosed 20-months after the initial surgery. A single surgical intervention was sufficient for treating this rare etiology. We herein present the case and discuss the available literature on the diagnosis and treatment of such complication.